THE USE OF E-MIND MAP IN ONLINE THINK-PAIR-SHARE-BASED READING LEARNING ON STUDENTS’ READING COMPREHENSION - Hardiyanti, Ni Nengah; Myartawan, I Putu Ngurah Wage; Hadisaputra, I Nyoman Pasek (Universitas Pendidikan Ganesha, 2021)
There are still many students who do not like reading. Students feel that reading is a tiring activity, so students rarely have the intention to read. Students feel bored when reading and make students fast. This is the main reason why students do not like to read. This study aims to analyse the effectiveness of using e-mind maps in online reading learning based on Think-Pair-Share on the reading comprehension of Indonesian EFL students. This research is a pre-experimental study with a one-group pretest-posttest design. The sample consists of 32 class students. The techniques used to collect data are observation and interviews. Data were collected through pretest and posttest and analysed using descriptive and inferential statistics assisted by SPSS version 24. The results showed that the average posttest score of students was 91.13, which was higher than the average student pretest score of 75.72, and there were significant differences. The important difference between the mean pretest and posttest scores (Sig. (two-sided) was .000 < .05). Therefore, it can be said that the e-mind map in online reading learning based on Think-Pair-Share has a positive and significant effect on the reading comprehension of Indonesian EFL students. The research implication is that teachers can use e-mind map integration in online Think-Pair-Share settings. The application of e-mind in online Think-Pair-Share settings can facilitate students in learning and create a pleasant learning atmosphere so as to improve students’ reading comprehension, especially in learning English skills such as speaking, listening, and writing.